Evaluation of Job Satisfaction and Retention of Female Uniformed Personnel at The Civil Relations Service as A Result of Gender-Responsive Programs - Angulo, Portia S.; Beloro, Riza O.; Cruz, Hernando A.; Quimson, Jennifer S. (International Journal of Multidisciplinary: Applied Business and Education Research, 2023)
This research paper aims to measure the job satisfaction of female uniformed personnel and determine whether Gender and Development (GAD) policies and programs affect their retirement plans in military service. Moreover, it seeks to identify courses of action that could be implemented in the organization to further strengthen its GAD policies and programs. This study used a descriptive method for research with the assistance of a questionnaire as the main tool to gather data from the respondents. To examine the data, frequency distribution was used to determine the demographic profile of the respondents; Weighted Mean was used to assess the implementation and effectiveness of GAD programs and initiatives within the organization as well as to assess the job satisfaction on the promotion of women empowerment and participation; and Spearman Rank Correlation was used to measure the association between the level of satisfaction of female soldiers across age, rank, and civil status in terms of retention. Based on the result of the study, the implemented GAD policies and programs in the Civil Relations Service (CRS) significantly impact the retention of uniformed women and effectively address gender-related issues affecting women in the service. Furthermore, the study reveals that female uniformed personnel's satisfaction with the promotion of women empowerment and participation is a critical factor affecting their retention intentions. The researchers recommend that the organization develop policies and initiatives more responsive to the demands of the CRS female soldier. It's necessary to carry out a gender audit to determine the overall structure of the institution.